Chemical Composition, Antibacterial Activity and Mechanism of Action of Oil and Phenolics from AOF (Alpinia oxyphylla Miq.) - Chen, W.X.; Wang, D. (Asian Journal of Chemistry, 2014)
In this study, antibacterial activity of the oils, phenolics and crude extracts were tested against two Gram-positive (S. aureus, B. subtilis) and one Gram-negative (E. coli) bacteria by disc diffusion method and determining their minimum inhibitory concentration (MIC) values. The inhibition zones and MIC values for bacterial strains, were sensitive to the essential oil, phenolics and extracts of strains, were in the range of 8.2-21.8 mm and 156.25-1250 μg/mL, respectively. The significant antibacterial activities, relationship between three different samples, mechanism of the antibacterial activity was also tested in bacteria growth kinetic and SEM. Moreover, to identify the components of the phenolics and oil, the phenolic composition was determined by HPLC-DAD and oil was determined by GC-MS. Among them, catechin, sygric acid, rutin, ellagic acid, chlorogenic acid, nootkatone, b-humulene, 8,9-dehydro cycloisolongifolene, etc. was determined, which was considered as the potential effective antibacterial composition.